Electronic Nose (E-Nose) for Quality Detection of Tuna (Thunnus thynnus) Contaminated Bacteria - Astuti, Suryani Dyah; Muhamad, Alfian Baggraf; Rahmatillah, Akif; Yaqubi, Ahmad Khalil; Susilo, Yunus; Aji , Angger Krisna (Institute of Topical Disease Universitas Airlangga, 2023)
Tuna (Thunnus thynnus) is a food that is often consumed raw to support raw food diet activities, so it has the potential to be contaminated with Salmonella typhi bacteria. Fish can be contaminated by bacteria due to their high water and protein content. Indonesia is the world's main tuna producer. Salmonella typhi detection in fresh tuna in Indonesia must be negative for Salmonella microbial contamination in order to meet food safety requirements. Microbial testing has drawbacks, such as long delays. An electronic nose was used to detect Salmonella typhi bacteria in tuna fish. The sample used consisted of 3 kinds of samples: Salmonella typhi bacteria, tuna, and tuna with Salmonella typhi contamination. The research was conducted with a shelf life of 48 hours and a sensing period every 6 hours with a sensor array of 8 sensors. The sensor output data is processed using the PCA (Principal Component Analysis) method. Through the PCA method, each variation of bacterial treatment can be classified. The result of the cumulative percentage variance of the two main components (PC) in the classification test between Salmonella typhi, tuna, and tuna with Salmonella typhi bacteria contamination was 90.5%. The most influential sensors in this study are TGS 825 for PC1 with a loading value of 0.625 and TGS 826 for PC2 with a loading value of -0.753. Therefore, it can be concluded that an electronic nose can classify between pure tuna and tuna contaminated with Salmonella typhi bacteria.